2014
DOI: 10.1111/jocs.12469
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous Venous Graft Pseudoaneurysm: A Review of the Literature

Abstract: Saphenous vein graft (SVG) pseudoaneurysm is a rare complication of coronary artery bypass graft (CABG) surgery. A review of literature indicates that almost one third of patients are asymptomatic at detection and a history of operative complications and need for re-exploration after the initial surgery may serve as useful predictors for the development of this rare complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 11 publications
2
20
0
1
Order By: Relevance
“…In a 2015 systematic review of SVG pseudo-aneurysms, Smer et al reported that 48.6% cases presented with chest pain, followed by an asymptomatic presentation in 30.5% of the patients. A majority of the reported symptomatic cases were male, presenting between 11 and 20 years after CABG [7]. Other extreme presentations are present in literature, with pseudo-aneurysms presenting as superior vena cava syndrome secondary to direct compression [10] or even large lung masses [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2015 systematic review of SVG pseudo-aneurysms, Smer et al reported that 48.6% cases presented with chest pain, followed by an asymptomatic presentation in 30.5% of the patients. A majority of the reported symptomatic cases were male, presenting between 11 and 20 years after CABG [7]. Other extreme presentations are present in literature, with pseudo-aneurysms presenting as superior vena cava syndrome secondary to direct compression [10] or even large lung masses [11].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of pseudo-aneurysm after CABG has been reported to be < 1% in one case series, and rupture occurs in about 11% of the reported cases [7,8]. We report a case of a 76-year-old man presenting with acute onset chest pain and elevated biomarker levels, who was found to have a ruptured SVG pseudo-aneurysm at its junction with ascending aorta, 15 years after initial CABG surgery.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The other relatively common iatrogenic VFA occurs as a complication of venous graft surgery. In these settings, vascular trauma at the time of implantation or issues with the surgical technique create the environment for venous leak . Graft VFAs are commonly reported as a result of coronary artery bypass graft surgery .…”
Section: Discussionmentioning
confidence: 99%
“…In these settings, vascular trauma at the time of implantation or issues with the surgical technique create the environment for venous leak . Graft VFAs are commonly reported as a result of coronary artery bypass graft surgery . VFAs have also been rarely reported secondary to intra‐venous catheterisation .…”
Section: Discussionmentioning
confidence: 99%